The Effect of Capital Intensity and Company Size on the Quality of ESG Disclosure with the Characteristics of Public Accounting Firms as Mediation Variables - Yasmin; Sofie (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of capital intensity and firm size on the quality of Environmental, Social, and Governance (ESG) disclosure, with public accounting firm characteristics as a mediating variable. This research employs a quantitative approach with an explanatory research design. The data used are secondary data in the form of panel data from consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling, resulting in 30 companies. Data analysis was conducted using panel data regression with the assistance of EViews software, and mediation testing was performed using the Sobel test. The results show that capital intensity has a significant negative effect on the quality of ESG disclosure. In contrast, firm size has a positive and significant effect on the quality of ESG disclosure. Public accounting firm characteristics also have a positive and significant effect on ESG disclosure quality. Furthermore, capital intensity negatively affects public accounting firm characteristics, while firm size has a positive effect. The mediation test results indicate that public accounting firm characteristics significantly mediate the relationship between capital intensity and firm size and ESG disclosure quality. Simultaneously, capital intensity and firm size also have a significant effect on ESG disclosure quality.